Automated Network Protocol Evaluation - the Potsdam Wireless Testbed - Fudickar, Sebastian; Schnor, Bettina (International Journal of Computing, 2011)
The Potsdam Wireless Testbed supports validation and evaluation of Wi-Fi radio stacks and wireless applications in environments with heterogeneous hardware. In contrast to simulators, wireless testbeds support the network stack validation with specific radio chipsets and radio signal propagations. Furthermore, wireless testbeds unburden programmers from manually updating software on nodes. Scheduled test-runs are executed automatically for a defined duration including compilation and deployment of the protocols and measurement scripts as well as collection of measurement results and log files. The testbed supports heterogeneous processor architectures and radio chipsets via internal cross compilation. The developer can overview the visualized results of its validation and therefore can focus on the code and the results. Next to the support of several device and processor architectures, the Potsdam Wireless Testbed is intended to support additional radio frequency ranges as well as mobile device.